Family Education in the Qur’an: A Descriptive-Qualitative Analysis of Al-Maturidi’s Al-Ta’wilat Al-Maturidiyah and Its Relevance to Modern Family Life - Muchtar, M. Ilham; Wasalmi; Hulawa, Djeprin E.; Syafi'i, Achmad Ghozali; Supriaji, Ujud; Rahman; Mugiarto (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2024)
This article delves into the concept of family education as outlined in the Qur’an from the perspective of Al-Maturidi. Employing a descriptive-qualitative method and categorized as library research, this study gathers data by meticulously examining various relevant references. These include Al-Maturidi’s work, al-Ta’wilat al-Maturidiyah fi Bayani Usl Ahl al-Sunnah wa Usul al-Tauhid, alongside books, articles, and other supporting documents. The data analysis is conducted using content analysis methods. The findings suggest that Al-Maturidi allocates substantial discussion to this topic. This focus is understandable, given that this exegetical work emerged within the context of theological contestations among Sunni, Mu’tazila, and other kalam (theological) schools. Interpretations from this era often exhibit subjectivity, aiming to undermine opposing schools of thought while legitimizing their own. Despite this, a review of various other commentaries highlights the critical role of the family in educating children from sociological, psychological, and religious perspectives. However, many families struggle to fulfill this role, resulting in issues such as juvenile delinquency and deficiencies in educational and communicative abilities. To enhance the effectiveness of family education, efforts must be made to foster family harmony, expand educational awareness, strengthen families’ problem-solving and conflict resolution capabilities, and effectively convey educational messages to children